Máscaras no vazio: criação de canções experimentais a partir da prática interativa com violão e voz - Rubens Pereira de Souza Silva (2022)
This work addresses the process of creating the set of songs entitled Máscaras no Vazio (Masks in the Void), analyzing the technical-creative processes chosen and explored in a context of social isolation. The poetic starting point was the elaboration of texts containing reflections on isolation, explored later within the potentials and limitations offered by the combination of voice, guitar, and an interactive musical system, developed in the Max programming language. The methodology used is close to the concept of research-creation formulated by Stévance and Lacasse (2017), where reflections on the universe of the song and the exploratory practices of interactive audio processing support the creative process of this work. The great challenge, or the main objective of this research, consisted of developing interactive strategies for the combined use of the system, the voice, and the guitar. Audio descriptors furnish the basis for varied controls, whose activity in different instants of the performance is determined by presets; three digital pedals complete the control section. The resulting sound combines the direct sounds (and buffers recorded during the performance) of the voice and guitar with various transformations, such as granulation, artificial prolongation, and variable delay lines. The dissertation resulted in the audio recording of one specific performance of the songs and the discussion of different issues raised during the creative process.